CRIPTO antagonist ALK4(L75A)-Fc inhibits breast cancer cell plasticity and adaptation to stress - Balcioglu, Ozlen (Breast Cancer Res, 2020)
BACKGROUND: CRIPTO is a multi-functional signaling protein that promotes stemness and oncogenesis. We previously developed a CRIPTO antagonist, ALK4(L75A)-Fc, and showed that it causes loss of the stem cell phenotype in normal mammary epithelia suggesting it may similarly inhibit CRIPTO-dependent plasticity in breast cancer cells. METHODS: We focused on two triple negative breast cancer cell lines (MDA-MB-231 and MDA-MB-468) to measure the effects of ALK4(L75A)-Fc on cancer cell behavior under nutrient deprivation and endoplasmic reticulum stress. We characterized the proliferation and migration of these cells in vitro using time-lapse microscopy and characterized stress-dependent changes in the levels and distribution of CRIPTO signaling mediators and cancer stem cell markers. We also assessed the effects of ALK4(L75A)-Fc on proliferation, EMT, and stem cell markers in vivo as well as on tumor growth and metastasis using inducible lentiviral delivery or systemic administration of purified ALK4(L75A)-Fc, which represents a candidate therapeutic approach. RESULTS: ALK4(L75A)-Fc inhibited adaptive responses of breast cancer cells under conditions of nutrient and ER stress and reduced their proliferation, migration, clonogenicity, and expression of EMT and cancer stem cell markers. ALK4(L75A)-Fc also inhibited proliferation of human breast cancer cells in stressed tumor microenvironments in xenografts and reduced both primary tumor size and metastatic burden. CONCLUSIONS: Cancer cell adaptation to stresses such as nutrient deprivation, hypoxia, and chemotherapy can critically contribute to dormancy, metastasis, therapy resistance, and recurrence. Identifying mechanisms that govern cellular adaptation, plasticity, and the emergence of stem-like cancer cells may be key to effective anticancer therapies. Results presented here indicate that targeting CRIPTO with ALK4(L75A)-Fc may have potential as such a therapy since it inhibits breast cancer cell adaptation to microenvironmental challenges and associated stem-like and EMT phenotypes.